Finding Letter Game to Improve Early Literacy Skills in 4-5 Year Old Children at Yasmin Preschool, Jember - Wardatun Jamilah; Wasminingsih (MANDAILING GLOBAL EDUKASIA, 2025)
This research aims to improve early literacy skills in children aged 4-5 years at PAUD Yasmin through the use of games. Finding Letter